REGIONAL STUDIES AS A COMPLEX OF RESEARCH AND EDUCATIONAL DISCIPLINES IN THE LIGHT OF INTERDISCIPLINARITY - Olga Zinevich (Сравнительная политика, 2015)
The paper is intended to answer the question about the necessity to distinguish between various approaches to reconstruction of interdisciplinarity of regional studies within the scientific and educational fields. There is a problem of establishing of such an interdisciplinary links in teaching practice and in application of research results in training programs. Within the educational program it is possible to introduce a lot of various interdisciplinary fields, when different sciences may play a leading role to represent the context. It is shown that historical disciplines play an important role within regional studies.